Implementasi Kebijakan Tentang Perubahan Nomenklatur Jabatan Pelaksana : (Studi Kasus Bagian Organisasi Sekretariat Daerah Kota Surabaya) - Saskia Nisa Setiaatmitha; Anggraeny Puspaningtyas (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
In recent years, the Surabaya City Government has revised the nomenclature of executive positions in various government agencies. Implementation of policies on changes in position nomenclature is not always easy. Decree of the Minister of Administrative Reform and Bureaucratic Reform Number 11 of 2024 concerning Executive Positions for State Civil Apparatus within Government Agencies as the latest legal basis for the use of nomenclature and job classes for agency employees. This research is a descriptive qualitative approach that will provide in-depth insight into how the implementation of policies on changes in the nomenclature of executive positions occurs in the Organization Section of the Surabaya City Regional Secretariat, as well as the factors that influence it. The Organization Section has four variables as factors for successful policy implementation, namely communication, resources, disposition, and bureaucratic structure. The variables have been realized very well, but it is gradual and takes time. Recommendations from this study emphasize the importance of maintaining the synergy of leaders and staff to implement all bureaucratic reform activities. Thus, this research provides valuable insights for other agencies in improving the effectiveness of policy implementation related to changes in the nomenclature of executive positions within the Surabaya City government.